(untitled) (Ustozlar uchun, 2026)
Artificial Intelligence (AI) has emerged as a transformative force in modern education, significantly influencing language learning processes. This study examines the role of AI technologies in enhancing second language acquisition, focusing on personalized learning, adaptive feedback, and learner engagement. Using a qualitative-analytical approach, the research reviews existing literature and practical applications of AI-driven tools in language education.[1] The findings indicate that AI facilitates more efficient and individualized learning experiences by providing instant feedback, tailored content, and interactive environments. However, challenges such as over-reliance on technology, reduced human interaction, and data privacy concerns are also identified. The study concludes that while AI offers significant advantages, its integration into language learning must be balanced with traditional pedagogical approaches.